Characterization of Voltage Sags and its Mitigation Using Custom Power Devices in Emerging Power System - Ravindra Kumar; Surya Prakash Singh; Bindeshwar Singh; Ravi Prakash Vishvakarma (Bulletin of Electrical Engineering and Informatics, 2012)
Voltage sags are short duration reductions in RMS voltage caused by short circuits, overloads and starting of large motors. Voltage sag is much more of a global problem. For proper analysis and mitigation of voltage sag, their characterization is important. The magnitude and durations are main characteristics of voltage sag. In this paper voltage sag and their characteristics have been presented in a comprehensive way. How voltage sags occur, what are their characteristics and impact on equipments behavior for different conditions. Through voltage source converters, it is possible to compensate for the drop in system voltage or even to temporarily take over the supply completely. The shunt and series controllers are based on power-electronic voltage source converters. For a full compensation both reactive and active power are needed. Only not for deep voltage sags but it is possible to compensate the drop in voltage magnitude by injecting reactive power only.